Matrix Type Transdermal Delivery System of Diclofenac Potassium-Skin Permeation and Pharmacokinetic Profile - Aamir, M.F.; Ahmad, M.; Murtaza, G.; Khan, S.A. (Asian Journal of Chemistry, 2011)
The aim of this study is to evaluate and compare matrix type patch formulations of diclofenac potassium, prepared by hydroxyl-propylmethylcellulose (HPMC 4000 cps), polyvinylpyrolidine (PVP K-30) and ammonio-methacrylate copolymer type A (Eudragit RL-100). The effect of various skin permeation enhancers on permeation characteristics of the diclofenac potassium from the prepared formulations through hairless abdominal rabbit skin was studied by using modified Franz diffusion cell. The patch formulations were compared with formulation controls (without enhancers). The cumulative amounts permeated and the fluxes were higher for the prepared formulations as compared to the controls. Skin permeation studies revealed better skin permeation characteristics of diclofenac potassium using isopropyl myristate than isopropyl palmitate and Tween 80. The cumulative amount permeated at 36 h (μg/cm2), steady-state flux Jss (μg/cm2 h), lag time tL (h), permeability coefficient kp (cm/s) and diffusion coefficient D (cm2/s) were determined for the prepared formulations in comparison with the controls. Skin permeation enhancers like isopropyl myristate (IPM), isopropyl palmitate (IPP) and nonionic surfactant (Tween 80) showed significant (p < 0.05) increment in the permeation of diclofenac potassium. The pharmacokinetic parameters of the optimized formulation (F4) were calculated from the blood levels of the drug revealed a profile typical of sustained release formulation with the ability to maintain adequate plasma levels for 24 h (i.e., up to the next application). AUC(0-24), Tmax and Cmax were 28.59 ± 5.34 ng h/mL, 5 h ± 1.1 and 2.606 ± 0.21 ng mL-1, respectively. The amount of drug bioavailable for targeting the site of action is higher than that of market control. Based on experimental results, preparation of 5 % diclofenac potassium matrix type patch formulation containing isopropyl myristate is promising.